Three-Dimensional Self-assembled Hairball-Like VS4 as High-Capacity Anodes for Sodium-Ion Batteries - Ding, Shuangshuang; Zhou, Bingxin; Chen, Changmiao; Huang, Zhao; Li, Pengchao; Wang, Shuangyin; Cao, Guozhong; Zhang, Ming (Nano-Micro Letters, 2020)
Sodium-ion batteries (SIBs) are considered to be attractive candidates for large-scale energy storage systems because of their rich earth abundance and consistent performance. However, there are still challenges in developing desirable anode materials that can accommodate rapid and stable insertion/extraction of Na+ and can exhibit excellent electrochemical performance. Herein, the self-assembled hairball-like VS4 as anodes of SIBs exhibits high discharge capacity (660 and 589 mAh g−1 at 1 and 3 A g−1, respectively) and excellent rate property (about 100% retention at 10 and 20 A g−1 after 1000 cycles) at room temperature. Moreover, the VS4 can also exhibit 591 mAh g−1 at 1 A g−1 after 600 cycles at 0 °C. An unlike traditional mechanism of VS4 for Na+ storage was proposed according to the dates of ex situ characterization, cyclic voltammetry, and electrochemical kinetic analysis. The capacities of the final stabilization stage are provided by the reactions of reversible transformation between Na2S and S, which were considered the reaction mechanisms of Na–S batteries. This work can provide a basis for the synthesis and application of sulfur-rich compounds in fields of batteries, semiconductor devices, and catalysts. Highlights: 1 The unique hairball-like VS4 composed of spiral nanowires was successively constructed through a one-step hydrothermal method. 2 The prepared hairball-like VS4 exhibits high capacity and long cycle stability for Na+ storage at room temperature, and it can tolerate drastic temperature changes. 3 The ex situ characterization and electrochemical kinetic analysis reveal that the storage mechanisms of VS4 changed with the increase in the number of cycles.